2021
DOI: 10.1021/acs.biomac.1c00314
|View full text |Cite
|
Sign up to set email alerts
|

Angiopep-2-Modified Carboxymethyl Chitosan-Based pH/Reduction Dual-Stimuli-Responsive Nanogels for Enhanced Targeting Glioblastoma

Abstract: Glioblastoma (GBM) is a fatal brain tumor with poor prognosis. Blood–brain barrier (BBB) prevents the effective delivery of chemotherapeutic agents to GBM. Herein, we developed a pH/reduction-sensitive carboxymethyl chitosan nanogel (CMCSN) modified by targeting peptide angiopep-2 (ANG) and loaded with doxorubicin (DOX). The multifunctional nanogel (DOX-ANG-CMCSN) exhibited good pH and reduction sensitivity, ideal stability, and biocompatibility. Its hydrodynamic diameter was 190 nm, drug loading was 12.7%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…The overexpression of receptors such as low-density lipoprotein receptors (LDLRs, including LRP-1, LRP-2, and LDLR), the transferrin receptor, and integrins on BBB and GBM cells provides a unique foundation for enhanced drug delivery to GBM. We found that apolipoprotein E peptide (ApoE, sequence: LRKLRKRLLLRKLRKRLLC), which is the tandem-repeat dimer peptide of the apolipoprotein E protein receptor-binding region, could bind to LDLRs with a high affinity and mediate marked BBB penetration and protein delivery for orthotopic GBM . Herein, we designed and explored small, smart, and LDLR-specific micelles based on the poly­(ethylene glycol)- b -poly­(ε-caprolactone- co -dithiolane trimethylene carbonate)-mefenamate (PEG-P­(CL-DTC)-MA) copolymer to efficiently load SF (LDLR-mSF) and to improve SF therapy of GBM by enhancing BBB penetration, GBM accumulation, and cell uptake (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of receptors such as low-density lipoprotein receptors (LDLRs, including LRP-1, LRP-2, and LDLR), the transferrin receptor, and integrins on BBB and GBM cells provides a unique foundation for enhanced drug delivery to GBM. We found that apolipoprotein E peptide (ApoE, sequence: LRKLRKRLLLRKLRKRLLC), which is the tandem-repeat dimer peptide of the apolipoprotein E protein receptor-binding region, could bind to LDLRs with a high affinity and mediate marked BBB penetration and protein delivery for orthotopic GBM . Herein, we designed and explored small, smart, and LDLR-specific micelles based on the poly­(ethylene glycol)- b -poly­(ε-caprolactone- co -dithiolane trimethylene carbonate)-mefenamate (PEG-P­(CL-DTC)-MA) copolymer to efficiently load SF (LDLR-mSF) and to improve SF therapy of GBM by enhancing BBB penetration, GBM accumulation, and cell uptake (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…All the results indicate that drug accumulation in the Ang2-Cou-6 liposomes was the highest in the bEnd.3 cells, illustrating the enhanced targeting effect enabled by the Ang2 modification. This may be mainly related to the endocytosis mediated by the binding of Ang2 to LRP receptors on bEnd.3 cells (Song et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…207,208 Vascular endothelin-2 (Angiopep-2, ANG) peptide from the aprotinin Kunitz domain can specifically target brain cells and bind to low-density lipoprotein receptor-associated protein-1 (LRP1) to achieve targeted delivery, which is overexpressed in the BBB and glioma. [209][210][211] IRGD (CRGD-KGPDC) binds to αvβ3 integrin, which is encapsulated by neuropilin 1 (NRP 1) after its cleavage, and then enters tumour cells through endocytosis. Due to the specificity of these two receptors, iRGD can target multiple tumour cells.…”
Section: Tumour-homing Cppsmentioning
confidence: 99%